Hakikat Negara, Syarat terbentuknya Negara, Bentuk Negara, dalam Pemerintahan, Sistem Kelembagaan Negara Indonesia Menurut UUD 1945. Hubungan Antar Lembaga Negara - Agus Rustama; Adhira Halim Ashari; Viola Zabrina Febriyanti; Febi Liontin; Naufalian Hafidz (Pusat Riset dan Inovasi Nasional, 2026)
State institutions play a primary role in governing and exercising power within a country. Indonesia, as a unitary state with a republican system, regulates the state's institutional structure through the 1945 Constitution, which serves as the supreme legal basis and guideline for state administration. The function of state institutions is to ensure that all aspects of government are implemented in accordance with the principles of law, justice, and public welfare. The state is not only considered a legal entity but also a social entity with specific functions and logic. The state's objectives are directed at balancing government power and citizen rights and accommodating the interests of individuals and the wider community. Following the amendments to the 1945 Constitution, Indonesia's institutional system underwent significant changes with the establishment of independent institutions that strengthen democracy, transparency, and accountability. Understanding the state's foundations, the requirements for formation, the form and system of government, and the relationships between institutions is crucial for maintaining Indonesia's constitutional order. Furthermore, public respect for state symbols and institutions contributes to strengthening unity and political stability, and realizing the ideals of a sovereign and prosperous nation.